A kulturális innováció területi terjedése - Kozma, Tamás (Tér és Társadalom, 1987)
The paper contains the results of a study on the spatial diffusion of a Hungarian popular professional magazine the Heti Világgazdaság or HVG (World Economical Weekly) which is published in Budapest from 1978. The findings can be summarized in the light of relevant literature as follows: The spatial expansion of subscriptions is influenced, though not definitely determined, by the distance of subscribers' homes from the capital. The so-called regional intellectual centres may counterbalance, or at least lessen, the effect of remoteness from Budapest but their absence virtually multiplies it. The 19 counties of Hungary were grouped – on the basis of their initial subscription rates and subscription dynamics – into four classes: the first class demonstrated a slow development from a low level of subscription rate; the second moved from a low level upwards at a rapid pace; the third class of counties shifted from a high level with little dynamics; and finally the fourth group displayed high levels of both subscription rate and dynamics. The initial subscription rate was found to be influenced significantly by the population size of settlements (and other, yet undisclosed, social factors) while its dynamics could be related t the 'irradiation' effect of intellectual centres: either the vicinity of the capital or the accessibility of a regional centre. Certain extreme cases like the high initial subscription rates in Csongrád county leven without the regional centre Szeged) or the rapid diffusion of subscriptions in the villages of Tolna county need further thorough investigations. It was apparently possible to identify some 'innovation centres' within Hungary on the basis of the spatial extent and the diffusion dynamics of subscriptions. Areas which were left out of this innovation process could also be identified. Such areas were found in the regions of small villages within South-Transdanubia, firstly in Baranya county as well as in North-Transdanubia, around Pápa. In North-Hungary, the settlements of Abaúj and Zemplén while in the eastern end the villages of Szatmár seem to be in a similar situation. Further in-depth research is therefore thought to be required into the backwardness in North-Transdanubia and into the 'innovation centres' in South-Alföld. Similarly, it is necessary to call the attention to certain 'secondary' regions which are important in the transmission of innovation e.g. Tab and its environs in Somogy county or Tolna county which was already mentioned for the rapid innovation diffusion there.